Utilization of Euryale ferox Salisbury seed shell for removal of basic fuchsin dye from water: equilibrium and kinetics investigation. Issue 44 (26th May 2017) - Kalita, S.; Pathak, M.; Devi, G.; Sarma, H. P.; Bhattacharyya, K. G.; Sarma, A.; Devi, A.
Abstract : Euryale ferox Salisbury ( E. ferox ) is an environmentally and economically important wetland macrophyte. Abstract : Euryale ferox Salisbury ( E. ferox ) is an environmentally and economically important wetland macrophyte. This paper investigates the adsorption of a carcinogenic dye, basic fuchsin in the aqueous phase onto the hard shell of Euryale ferox seeds so as to establish the thrown away residue as a novel, efficient, bio-friendly and economically low-cost alternative adsorbent against other expensive adsorbents. Characterization of the bioadsorbent was carried out by TGA, SEM, FTIR and Zetasizer analyses. Zeta potential analysis showed good stability of the biomaterial around neutral pH. The operating variables such as adsorbent amount, adsorbate concentration, contact time, pH and temperature were optimized in a batch system. The maximum biosorption capacity of E. ferox was found to be 19.48 mg g −1 which could remove as much as 97.4% of the dye from an aqueous solution of concentration 40 mg L −1 at 298 K. Isothermal and kinetic data fitted best to Freundlich and pseudo second order models respectively. The thermodynamic study revealed the exothermic and spontaneous nature of the adsorption process.